(untitled) (College of Basic Education Research Journal, 2025)
This research dealt with method taken by Mohammed Amin Al-Khatib Al-Omari in his book ((Tijan Al-Bayan in quran problems)) This research included an introduction, six objects and a finale. Introduction dealt with title, relevance and plan of research As well as manner in which author committed and adopted it in his book. Six objects also talked about a brief biography of Al-Khatib Al-Omari.Then research was concluded with most important findings,Then enlisted sources that were relied upon in writing this research